The Influence of Product Quality, Promotion and Design on Purchase Decisions for Yamaha Nmax Motor Vehicles SPSS Application Based - Nasution, Atika Aini; Baginda Harahap; Zuriani Ritonga; Nurjannah (PT Inovasi Pratama Internasional, 2022)
This study aims to analyze the influence of product quality, promotion and design on purchasing decisions for Yamaha Nmax motorcycle products and analyze the variables that have the most dominant influence on purchasing decisions for Yamaha Nmax motorcycle products in the community in the Medan City. From the results of the classical assumption analysis, the normality test with the Kolmogorov-Smirnov was obtained significantly greater than 0.05, which means that the data distribution is normal. Multicollinearity test obtained VIF and Tolerance values ​​that are close to one so that it can be concluded that the regression model has no multicollinearity problem, while the heteroscedasticity test using the Glejser method states there is no problem. Based on the results of multiple linear regression analysis from the t test, it was found that partially product quality had a significant effect on purchasing decisions for Yamaha Nmax motorcycle products, while promotion and design had a significant effect on the 5% level. From the results of the F test that simultaneously product quality, promotion and design have a significant effect on purchasing decisions for Yamaha Nmax motorcycle products where the value of F count > F table . Product quality has the most dominant influence on purchasing decisions for Yamaha Nmax motorcycle products. The R square value is 0.255, which means that the dependent variable can be explained by the independent variable by 25.5% while the remaining 74.5% is explained by other variables outside the model.